School leaders as part of the governing education systems: the PISA Report and causal analysis - Alcañiz Miñano, Vicente; Sanz Labrador, Ismael; Doncel Pedrera, Luis Miguel (Avances en Supervisión Educativa, 2024)
The article analyzes the main findings provided by the OECD Programme for International Student Assessment (PISA), in relation to school management. The main conclusions of the PISA study are linked to the latest causal findings provided by research articles on the effect of a good management team on the quality of education and student outcomes and learning.
Keywords: Educational system; management team; principals; leadership; PISA